The Role of Edge Dislocations on the Red Luminescence of ZnO Films Deposited by RF-Sputtering - Felix, Rocio (2017)
The existence of extended defects (i.e., dislocations) in inorganic semiconductors, such as GaN or ZnO, responsible for broad emission peaks in photoluminescence analysis remains unresolved. The possible assignments of these luminescence bands are still matter of discussion. In this study, two different zinc oxide samples, grown under different oxygen partial pressures and substrate temperatures, are presented. Epitaxial and structural properties were analysed by means of X-ray diffraction and transmission electron microscopy techniques. They confirm that the layers are single-phase with a good crystalline quality. Nevertheless, a different density of threading dislocations, with a higher contribution of edge dislocations, was found. Photoluminescence spectroscopy has been used to investigate the optical properties. The steady state luminescence spectra performed at 14K evidenced the donor bound exciton recombination and deep green and red emission bands. The red band with a maximum at 1.78 eV was found to be stronger in the sample grown at lower oxygen pressure which also shows higher density of threading dislocations. From the temperature and excitation density dependence of the red band, a donor acceptor pair recombination model was proposed, where hydrogen and zinc vacancies are strong candidates for the donor and acceptor species, respectively.